2019
DOI: 10.1523/jneurosci.1167-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Recurrent Absence Seizure-like Events in Wild-Caught Rats

Abstract: Absence epilepsy is a heritable human neurological disorder characterized by brief nonconvulsive seizures with behavioral arrest, moderate-to-severe loss of consciousness (absence), and distinct spike-wave discharges (SWDs) in the EEG and electrocorticogram (ECoG). Genetic models of this disorder have been created by selectively inbreeding rats for absence seizure-like events with similar electrical and behavioral characteristics. However, these events are also common in outbred laboratory rats, raising concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 43 publications
(72 reference statements)
3
25
0
2
Order By: Relevance
“…SWDs were significantly more prevalent and had longer durations in Syngap +/Δ-GAP rats when compared to age-matched WT littermates, and similar to previous reports, these SWDs do not occur during our behavioural tasks and were suppressed by ethosuximide (Shaw, 2004(Shaw, , 2007Terzioglu et al, 2006). Although SWDs were found in our WT animals, these were at a frequency similar to previous reports (Taylor et al, 2019). Moreover, the higher incidence of SWDs in mutants suggests that the deletion of the C2/GAP domain in rats drives cortical networks to a state of hyperexcitability leading to absence-like electrophysiological phenomena.…”
Section: Discussionsupporting
confidence: 91%
“…SWDs were significantly more prevalent and had longer durations in Syngap +/Δ-GAP rats when compared to age-matched WT littermates, and similar to previous reports, these SWDs do not occur during our behavioural tasks and were suppressed by ethosuximide (Shaw, 2004(Shaw, , 2007Terzioglu et al, 2006). Although SWDs were found in our WT animals, these were at a frequency similar to previous reports (Taylor et al, 2019). Moreover, the higher incidence of SWDs in mutants suggests that the deletion of the C2/GAP domain in rats drives cortical networks to a state of hyperexcitability leading to absence-like electrophysiological phenomena.…”
Section: Discussionsupporting
confidence: 91%
“…A combined EEG video study showed that during the cortical expressed SWDs WAG/ Rij rats show head tilting, twitching of the vibrissae, accelerated breathing, and occasional eye blinks, and facial myoclonus in otherwise immobile animals (van Luijtelaar and Coenen, 1986). Close inspecting of the EEG oscillations as presented in Taylor et al (2019) shows that only a minority of the illustrated SWDs in the wild rats could classify as SWDs according to our criteria and characteristic features. Relevant and typical is that SWDs appear as bilateral symmetrical generalized, minimal duration 1 s, asymmetric morphology with a sharp large amplitude negative peak with a duration between 25 and 35 ms, this peak is most pronounced expressed at the frontal cortex and a clear negative wave (40-60 ms), less well expressed at the frontal cortex but more at the thalamic VPM, with a "sudden" appearance from a normal appearing background and without a waxing and waning pattern).…”
Section: Are All 8 Hz Oscillations Swds?mentioning
confidence: 82%
“…A relevant question that was recently raised again is whether all oscillations in the 8 Hz domain, mimicking to some extent the SWDs in GAERS and WAG/Rij rats and are known for a long term to be present in different outbred strains of rats (Willoughby and Mackenzie, 1992;Marescaux et al, 1984;van Luijtelaar et al, 1994) and now noticed in wild rats, should be indeed considered as genuine epileptic SWDs (Taylor et al, 2017;Taylor et al, 2019). First, WAG/Rij rats have clinical concomitants during the SWDs, they are mild, and might be easily overlooked.…”
Section: Are All 8 Hz Oscillations Swds?mentioning
confidence: 99%
“…Важливим питанням, що залищаєтьcя відкритим, є визначення ритмічних розрядів частотою 8 Гц як таких, що мають відношення до СХР у щурів ліній GAERS та WAG/Rij, а також у генетично похідних змішаних ліній [39,80,98]. Подібне питання стає важливим при визначенні природи подібних СХР, що останнім часом зареєстровано у безпородних диких ліній щурів [69,70].…”
Section: медична інформатика медична інформатика та інженеріяunclassified
“…Так, одночасна реєстрація відео-та ЕЕГ засвідчила, що на тлі СХР, які реєстрували в корі головного мозку у WAG/Rij щурів спостергіаються характерні посмикування голови та вібрис, прискорене дихання, посмикування повік із закриттям ока, клонуси мязів морди на тлі завмирання тварини [76]. Аналіз ЕЕГ-картини наведений [70] свідчить, що тільки меншість ілюстрованих автором СХР у диких щурів може бути визнане в якості СХР. Зокрема для визнання приналежності до СХР потрібна одночасна, симетрична та білатеральна їх поява з мінімальною тривалістю комплексів в одну секунду, а також із характерною МЕДИЧНА ІНФОРМАТИКА МЕДИЧНА ІНФОРМАТИКА ТА ІНЖЕНЕРІЯ морфологією окремих розрядів, до якої відносяться гострий високоамплітудний спайк негативної полярності тривалістю 25-35 мс.…”
Section: медична інформатика медична інформатика та інженеріяunclassified